Amir Nasrullah - the butcher amir - Ermatova , Masuma (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Amir Nasrullo is remembered in history as one of the most prominent and, at the same time, one of the most ruthless rulers of the Bukhara Emirate. He became widely known among the people by the لقب “the Butcher Amir,” a reputation shaped by the harsh punishments, executions, and the uncompromising elimination of suspected opponents during his reign. This study examines Amir Nasrullo’s political activity, the strict measures he implemented to consolidate power, and his personal style of governance. It analyzes his efforts to centralize the state, his policies aimed at eliminating internal rivals, and the violence that accompanied these processes. The article also explores the events that contributed to his enduring image as the “Butcher Amir,” his reputation among the population, and his portrayal in historical sources. Overall, the study highlights the complexity and controversial nature of Amir Nasrullo’s personality, as well as his significant yet debated role in the history of the Bukhara Emirate.